2017
DOI: 10.1007/s11356-017-9701-2
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor gene transitions (c.-742C>T; c.1661G>A) and idiopathic male infertility: a case-control study with in silico and meta-analysis

Abstract: Aryl hydrocarbon receptor (AHR) is responsible for crucial events in male reproductive biology. Here, the association of the AHR transitions c.-742C>T and c.1661G>A with idiopathic male infertility was investigated in a case-control study, which is followed by a meta-analysis and a bioinformatic investigation. Blood and semen samples were obtained from a total of 135 idiopathic infertile men and 130 healthy controls. Participants were genotyped for the transitions using a PCR-RFLP method. A meta-analysis of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…The result was consistent with that rs339939442 locus was associated with the litter size of European pigs [8]. Previous research has also shown that the AHR gene influence estrous cycle and ovarian development and fertility [12,25,37]. Therefore, our results and previous results can suggest that the AHR gene has a certain role in the reproduction process.…”
Section: Discussionsupporting
confidence: 92%
“…The result was consistent with that rs339939442 locus was associated with the litter size of European pigs [8]. Previous research has also shown that the AHR gene influence estrous cycle and ovarian development and fertility [12,25,37]. Therefore, our results and previous results can suggest that the AHR gene has a certain role in the reproduction process.…”
Section: Discussionsupporting
confidence: 92%
“…Among these search results, 76 studies were excluded for full text review after screening titles and abstracts. Finally, 7 case–control studies involving 1247 cases and 1762 controls were included in this meta-analysis [19–25]. The studies were published from 2004 to 2017.…”
Section: Resultsmentioning
confidence: 99%